Assessment of the impacts of low-rise buildings (LRB) on the quality of the surrounding community the case of selected in-city LRBS in Metro Manila - Lauron, Olivia M. (School of Urban and Regional Planning, University of the Philippines Diliman, 2021)
This research is focused on the problem: "What are the impacts of LRBs on the quality of the surrounding community as perceived by the residents of the selected in-city LRBs in Metro Manila?". The study's main objective is to assess the impacts through the perception of the residents living up to 1,000m from the LRB development. The major impacts measured are impacts with regards to urban infrastructure (which includes parks and open spaces, identity of the neighborhood, and the overall physical environment), urban landscape (which includes public transportation access and traffic density, and drainage system), and local microclimate (which includes wind, shading, and temperature). A case study approach is utilized in the research wherein the surrounding community of Camarin Residences 1 in Caloocan City, Manggahan Residences 1 and 2 in Pasig City, and NGC Phase 4 Package 1 in in Quezon City are the study sites. Individual survey, key format interview (KII), and field observation were done as primary data collection. The research study showed that residents living around the LRB housing up to 500-meters away perceived negative impacts brought by the NHA LRB developments. These impacts include alterations in the urban landscape, overload in the urban infrastructure, and alteration in the local microclimate. Some negative impacts can also be observed up to 1,000-meters away from the LRB development but are minimal and not as noticeable as those within 500-meters. The research study also showed that the correlation of the distance of the residents to the LRB housing is inversely proportional with the number of impacts the residents perceive. The farther the houses are located with respect to the LRB housing, the less impact they observe.